Cascaded incremental nonlinear dynamic inversion trajectory following for a stratospheric airship in wind - Schneider, Leo; Souanef, Toufik; Whidborne, James F. (World Scientific Publishing, 2025)
This paper presents a guidance and control system for controlling the trajectory of a stratospheric unmanned airship using a cascaded Incremental Nonlinear Dynamic Inversion (INDI) method. The control system uses a two-loop cascaded INDI controller with virtual efforts and moments formulation to control both the airship attitude and velocity, while providing perturbation rejection properties. An active-set solver allocates the virtual controls to the airship propellers and aerodynamic surfaces while respecting the actuator bounds and rates saturation. The guidance system uses a Nonlinear Dynamic Inversion controller, where the position error dynamics formulation explicitly considers the lateral velocity of the airship, which enables it to counteract the wind influence. Simulation results demonstrate that the reference trajectory is precisely followed, even in the presence of unknown wind perturbations and both aerodynamic coefficients and mass and inertia parametric uncertainties through Monte-Carlo simulations.
Keywords: 4007 Control Engineering, Mechatronics and Robotics; 40 Engineering; 4017 Mechanical Engineering; 7 Affordable and Clean Energy; Airship; trajectory-following; guidance and control; incremental nonlinear dynamic inversion